A review of the bioactive ingredients of berries and their applications in curing diseases. (December 2021) - Bilawal, Akhunzada; Ishfaq, Muhammad; Gantumur, Munkh-Amgalan; Qayum, Abdul; Shi, Rujie; Fazilani, Saqib Ali; Anwar, Asif; Jiang, Zhanmei; Hou, Juncai
Abstract: Lethal diseases are the most common causes of death in the world that are mostly associated with nutritional imbalance and quality of life. However, the consumers' interest in nutraceutical-rich food, particularly vegetables and fruits, has been intensified by the relevance of nutrition in relation to human wellbeing. In this regard, berries are considered a rich source of human beneficiary phytochemicals, including phenolic acids, flavonoids, tannins, and stilbenes. The present review summarized the in vitro and in vitro biological properties of berries such as anti-Alzheimer, anti-diabetic, anti-inflammatory, anti-microbial, anti-neurodegenerative, and anti-cancerous presented in the last decade. Moreover, the physio-chemical properties of active ingredients of berries are discussed in the present review for better understanding. The evidences suggested that quinic acid, catechol, catechin, gallic acid, ellagic acid, anthocyanins, minerals, and few vitamins are the active ingredients of berries. These compounds possess many biological properties such as antioxidant and anti-inflammatory that could have preventive effects against cancer by inhibiting cell-proliferation, autophagy induction, and inducing apoptosis, anti-diabetes by inhibiting α-glucosidase, α-amylase, and dipeptidyl peptidase-4 expression, anti-Alzheimer's disease by reducing Aβ, BChE, AChE, and BACE-1 expression and nitrate generation. It concluded that berries extract showed remarkable results against different diseases. Still, some species should be studied more thoroughly for their biological activities. Graphical abstract: Image 1 Highlights: The biological activities of different types of berries were highlighted in the present review. Catechin quinic acid, gallic acid, anthocyanins, minerals, and few vitamins were the main active ingredients of berries. Berries significantly exhibit antioxidant, anti-inflammatory and anti-cancerous activities. Berries showed a protective effect in Alzheimer's disease by reducing Aβ, BChE, AChE, and BACE-1 expression. It was concluded that berries extract showed remarkable results against different diseases.